The struggle for inclusion: Muslim minorities and the democratic ethos - Ivarsflaten, Elisabeth (University of Chicago Press, 2022)
Intro -- Contents -- List of Figures -- Preface -- 1. Introduction -- A Note on Methodology and Data -- 2. Demonization and Diff erentiation -- 3. Respect -- 4. Speech as a Mirror of Dignity -- 5. The Construction of National Identities -- 6. Taking Part: Images of Citizenship -- 7. Liberal Values and Muslim Communities -- Appendix: A Methodological Note on the Validity of the IMCP Measure -- 8. A New Framework for the Study of Inclusive Politics -- 9. Invitations -- Acknowledgments -- Appendix: Documentation of Survey Experiments by Figure -- Notes -- Bibliography -- Data Sources -- Index.